Good Different - Kuyatt, Meg Eden (New York : Scholastic Press, 2023)
"Seventh-grader Selah Godfrey knows that to be "normal" she has to keep her feelings tightly controlled when people are around, but after hitting a fellow student, she needs to figure out just what makes her different--and why that is ok. Told in verse."--
Includes bibliographical references.
Keywords: Autistic girls -- Juvenile fiction; Neurodiversity -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Self-perception -- Juvenile fiction; Self-control in children -- Juvenile fiction; Emotions -- Juvenile fiction; Schools -- Juvenile fiction; Autistic girls -- Fiction; Neurodiversity -- Fiction; Self-actualization -- Fiction; Self-perception -- Fiction; Self-control in children -- Fiction; Emotions -- Fiction; Schools -- Fiction; Novels in verse